Prosedur Peminjaman Arsip Inaktif pada Unit Dokumen PT KAI DAOP 7 Madiun - Dhea Rahayu Anggraini; Tatiana Kristianingsih (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the procedure for borrowing inactive archives at the Document Unit of PT Kereta Api Indonesia (Persero) Daop 7 Madiun. The research uses a qualitative descriptive method through direct observation, interviews, and documentation during the internship period. The results show that the archive borrowing process was previously carried out without a written procedure, causing difficulties in tracking archive circulation, lack of administrative evidence, and potential risks of loss or damage. Therefore, a structured borrowing procedure was developed, including submission through official memo, verification process, archive retrieval, documentation using Google Form, and signing of borrowing reports. The implementation of this procedure improves administrative order, accountability, and efficiency in archive services. This study contributes to the development of archival management practices, especially in managing inactive archive borrowing systematically and sustainably.paragraph.